Longitudinal Study of Dental Environment Stressors Experienced by Undergraduate Dentistry Students - de Carvalho, Monica Moreno [UNESP]; de Oliveira, Vitória Parmejane [UNESP]; Sonoda, Celso Koogi [UNESP]; Miyahara, Glauco Issamu [UNESP]; Bernabé, Daniel Galera [UNESP]; Takamiya, Aline Satie [UNESP] (Wiley, 2025)
The aim of this investigation was to determine whether there were any changes in the stress factors of the dental environment between the first and last semesters of undergraduate study. This longitudinal and quantitative study was conducted on 84 undergraduates (60 females; 24 males) to analyze the sources of stress among dental students during their course. A modified version of dental environment stress (DES) questionnaire was used, consisting of 49 items describing stressors specifically relating to dental undergraduate training during the first and last semesters, evaluating the amount of stress on the five-point Likert scale. The average stress per student in the first semester was 86.51 (minimum: 46; maximum: 131), and the average stress per student was 73.80 (minimum: 30; maximum: 114) in the last semester. The domains preclinical and clinical training and workload had the highest stress rates in the first and last semesters. It was concluded that the amount and sources of stress change over time for first- and last-semester dental students, since those in their final semester showed lower levels of environmental stress.